Optical properties of highly n-doped germanium obtained by in situ doping and laser annealing. (26th October 2017) - Frigerio, J; Ballabio, A; Gallacher, K; Giliberti, V; Baldassarre, L; Millar, R; Milazzo, R; Maiolo, L; Minotti, A; Bottegoni, F; Biagioni, P; Paul, D; et al.
Abstract: High n-type doping in germanium is essential for many electronic and optoelectronic applications especially for high performance Ohmic contacts, lasing and mid-infrared plasmonics. We report on the combination of in situ doping and excimer laser annealing to improve the activation of phosphorous in germanium. An activated n-doping concentration of 8.8 × 10 19 cm −3 has been achieved starting from an incorporated phosphorous concentration of 1.1 × 10 20 cm −3 . Infrared reflectivity data fitted with a multi-layer Drude model indicate good uniformity over a 350 nm thick layer. Photoluminescence demonstrates clear bandgap narrowing and an increased ratio of direct to indirect bandgap emission confirming the high doping densities achieved.